2004
DOI: 10.1534/genetics.104.030296
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Quantitative Trait Loci Mapping With Cofactors and Application of Alternative Variants of the False Discovery Rate in an Enlarged Granddaughter Design

Abstract: The experimental power of a granddaughter design to detect quantitative trait loci (QTL) in dairy cattle is often limited by the availability of progeny-tested sires, by the ignoring of already identified QTL in the statistical analysis, and by the application of stringent experimentwise significance levels. This study describes an experiment that addressed these points. A large granddaughter design was set up that included sires from two countries (Germany and France), resulting in almost 2000 sires. The anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 31 publications
(6 reference statements)
4
34
0
Order By: Relevance
“…The QTL on BTA14 is in the region that includes DGAT1, which has an effect on net merit because of the economic value associated with milk components (Cole et al, 2010). The SCS findings are consistent with a QTL on BTA6 as previously reported by Bennewitz et al (2004) and Lund et al (2008). Chromosomes with nominal APDG P < 10 − 8 and numbers of grandsire families with t-values >3 for within-family contrasts are shown in Table 3 by chromosome.…”
Section: Weller Cole Vanraden and Wigganssupporting
confidence: 90%
“…The QTL on BTA14 is in the region that includes DGAT1, which has an effect on net merit because of the economic value associated with milk components (Cole et al, 2010). The SCS findings are consistent with a QTL on BTA6 as previously reported by Bennewitz et al (2004) and Lund et al (2008). Chromosomes with nominal APDG P < 10 − 8 and numbers of grandsire families with t-values >3 for within-family contrasts are shown in Table 3 by chromosome.…”
Section: Weller Cole Vanraden and Wigganssupporting
confidence: 90%
“…The "high heritability" in the present study, simulates the situation for most yield traits that are routinely measured in progeny testing of AI bulls in dairy cattle and "low heritability" resembles the heritability observed for disease traits. However, we did not observe an increase in power with cofactor analysis as reported earlier [1,3,16,18,20]. De Koning et al [3] reported, using cofactor analysis, that the initial number of five suggestive QTL had increased to eight significant QTL in a study with data with an average of 41 sons per sire and ranging from 21 to 82.…”
Section: Discussionsupporting
confidence: 72%
“…Using cofactors, they observed eight QTL exceeding the 5% genome-wise significance threshold. Bennewitz et al [1] also observed a 39% increase (from 18 to 25) in the number of QTL detected when cofactors were included in the model in comparison to single chromosome analyses. Schulman et al [16] reported 67% increase (from 6 to 10) in the number of QTL detected with cofactor analysis in comparison with single chromosome analysis.…”
Section: Introductionmentioning
confidence: 89%
“…The bovine BTN1A1 gene has been mapped to chromosome 23 (Taylor et al, 1996). In the same genome region, several QTL for health and production traits have been identified (Ashwell et al, 1997;Bennewitz et al, 2004). Butyrophilin might serve as a possible candidate influencing the variation in the detected QTL.…”
Section: Resultsmentioning
confidence: 99%